Pengaruh Locus Of Control, Integrity, Equity Sensitivity Dan Budaya Etis Organisasi Terhadap Perilaku Etis Mahasiswa Akuntansi - Sugiarta, Putu Agus; Werastuti, Desak Nyoman Sri (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2021)
Â This research aims to identify and obtain empirical evidence of the influence of locus of control, integrity, equity sensitivity, and organizational ethical culture of accounting student behavior. The type of this research is quantitative research with a design survey. This research was conducted on accounting students in Ganesha University of Education year 2020/2021 and also a sample count of 298 accounting students. Technique sample taken by purposive sampling. The data used in this research are types premier data taken from respondents through spreading the questionnaire on the google form.Data analysis uses software SPSS 21 Version for Windows to analyze the influence of independent variables on a dependent variable. From the result of the research analysis, it is obtained that locus of control, integrity, and equity sensitivity have a possitive influence ethical behavior than the ethical culture of an organization does no affect ethical behaviorÂ